Empowering the Community Through Candlenut Peeling Machine Training and Mentoring in Sembahe Village - Sembiring, Timbangen; Hamid, Muhammadin; Sianturi, Herty Afrina; Devi Yolanda Simangunsong; Maria Derani Ester Vania Situngkir; Ayu Wahyuni Batubara; Eva Purwanti; Martinez Lumbantobing; M Zidan Davy (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
A candlenut peeling machine is a technological innovation aimed at improving the efficiency of separating candlenut seeds from their shells. Hand-peeling candlenuts requires a lot of time and effort, and it carries a high risk of damaging the candlenut kernels due to uneven impact. This candlenut peeling machine is equipped with a mechanism that reduces seed damage and increases productivity. The machine can be operated manually or semi-automatically and works on the principle of utilizing pressure and friction to break the shell without damaging the seeds inside. Experimental results show that this machine has a high success rate in separating candlenut seeds from their shells and reduces the number of damaged seeds compared to traditional methods. The use of this machine aims to increase the productivity of candlenut farmers and add value to the candlenut processing industry.